Biomethane Production from Anaerobic Codigestion of Palm Oil Mill Effluent with Cattle Manure: A Review - Zaied, B. K.; Siddique, Md. Nurul Islam; Zularisam, A. W.; M. F., Ahmad; Y. M., Salih (Asian J. Chem, 2019)
Biogas is conventionally utilized in a gas engine to convert the chemical energy into electricity and into thermal energy for heating purposes and is also pumped into the natural gas grid line after impurities are removed. Biogas production from palm oil mill effluent is one of the best options for economic expansion and this would reduce environmental impacts in developing countries like Malaysia. This study aims to perform an analysis of the economic and environmental prospects of biogas production from the anaerobic codigestion method from palm oil mill effluent mixed with cow manure. Anaerobic codigestion technology is considered a practical process by which to overcome the complications of substance properties and system optimization in particular substance digestion operations. Comparisons among various treatment technologies of palm oil mill effluent and their applications have been studied thoroughly. The factors that affect biogas production, along with strategies for their improvement, were studied in present report. The economic feasibility of biogas plant where palm oil mill effluent and cattle manure are main substrates and anaerobic codigestion is the method, has been successfully predicted. Results revealed this might be more feasible if this technology is used on a large scale. Construction of the proposed biomethanization plant is economically feasible because it is projected that about a four-year return-on-investment will be achieved. In conclusion, the present work demonstrates a comprehensive feasibility framework by which to integrate the different features needed to enhance biomethane generation.